Penerapan Filosofi Adat Dalihan Natolu dalam Kehidupan Masyarakat Batak Toba di Kecamatan Pinggir Kabupaten Bengkalis - Fitri, Ayu; Isjoni; Bunari (CV Insan Kreasi Media, 2023)
the traditional philosophy of dalihan natolu is the philosophy of life of the Batak Toba community which has become a tradition in the life of the Batak Toba community since ancient times until now which has become the guideline and social order of the Batak Toba people, which has the three elements of the natolu pretext custom is sombah marhula-hula (respecting bones / uncles), mordongan tubu (surnames), elek marboru (coaxing girls). The purpose of the study is the philosophy of dalihan naktolu custom in the life of the Batak Toba people?, the existence of the natolu dalihan custom in the life of the Batak Toba community?, the change in the custom of the natolu dalihan in the life of the Batak Toba community?. This research uses a Qualitative Approach. A Qualitative approach was taken to determine the application of the Dalihan Natolu traditional philosophy in the life of the Batak Toba community in Pinggir District. The result of the research is that the traditional philosophy of dalihan natolu becomes the order of social life of the Batak Toba community which is a whole, harmonious, harmonious, and harmonious unit by establishing the three elements of the natolu dalihan custom, namely sombah marhula-hula (respecting bones / uncles), manat mardongan tubu (be careful who are friends / surnames), and elek marboru (persuading girls). The three elements of the natolu dalihan custom must maintain attitudes and attitudes towards others and respect each other's position in the application of the existence of the natolu dalihan custom which is always related in everyday life and in small events (mangupa, birth, member of the child's name, major events that have norms, attitudes and deeds applied in the natolu dalihan custom. The change of times that are the main factor in life, the lack of understanding / application of the three elements of the natolu dalihan custom will cause a marriage to occur and there will be a change in the custom of dalihan natolu, in life there is no attitude and respect for the position of the three elements that exist in the natolu dalihan custom